Designing Digital Productivity Support for Adults with ADHD: A User-Centered Study of Work and Study Barriers - From Survey Findings to an Interactive Prototype - Wei, Boyang; Yang, Yi (My University, 2026)
Adults with ADHD and people who experience persistent focus and organization difficulties often encounter barriers in everyday work and study contexts. These barriers can include difficulty organizing tasks, maintaining attention, switching between activities, remembering obligations, regulating emotion, and sustaining routines over time. Although many productivity tools and ADHD-friendly applications already exist, they often rely on assumptions that can be difficult for ADHD users to meet, such as stable planning ability, consistent routines, low setup effort, and positive responses to reminders or progress tracking. This thesis investigates how adults with ADHD or frequent focus and organization difficulties experience productivity-related barriers, how existing tools fail to meet those needs, and how user research can inform a more targeted digital support tool. The project follows a user-centered design process that combines literature review, survey research, design synthesis, and interactive prototyping. A survey with 69 valid responses was used as the main empirical basis for deriving design requirements. The findings show that participants had already tried many productivity and support tools, but still experienced difficulties related to communication paralysis, hyperfocus and difficulty switching, activation paralysis, emotional dysregulation, working memory gaps, sensory overload, and rejection sensitivity. The design response translates these findings into a focused prototype direction. The resulting concept explores support for messy thought capture, task breakdown, energy-aware planning, gentle feedback, mood and focus check-ins, and optional focus companionship. The prototype is not framed as a clinical intervention or a universal solution to ADHD. Instead, it functions as a research-informed design artifact that makes a possible model of ADHD-friendly productivity support concrete enough for reflection and user testing. An exploratory evaluation with 15 participants suggested that the mood check-in and focus session flows were relatively easy to complete, while the task breakdown flow showed both strong perceived value and clearer usability problems around discoverability and interaction clarity.
Keywords: ADHD, productivity tools, executive dysfunction, user-centered design, digital prototype, work and study barriers